(3Hjf GdfXQjI h GdJWHjbs - (3Ydj eLjO(B, (3GdMeGOjs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2010)
(3GdfehPL GdGbJUGOj eagheg , Jchjfg , NUGFUg h GfhGYg , GdYeb GdacQj h GdJGQjNj dfePL GdeSJNOe `` GdefJL , HfGA h JMdjd LOGhdGdeSJNOe `` GdefJL , GdJTGHc GdGbJUGOj , GSJNOGeGJ Jcfjc GdeSJNOe `` GdefJL , JWHjb efgLjI GdeSJNOe `` GdefJL Ydi hGbY GdJOabGJ GdHjfjI GdJLGQjI GdYQHjI , OQGSI JWHjbjI dJTNjU GdbWGYGJ GdeMhQjI aj GdGbJUGO GdYQGbj , OQGSI JMdjdjI JWHjbjI debGjjS GdJTGHc GdGeGej h GdNdaj aj GdGbJUGO GdYQGbj h JMdjd eDTQGJ GdLPH GdCeGej Ydi GdeSJhi GdbWGYj (B" (3MGdI GdUfGYI GdJMhjdjI aj GdYQGb(B"s
(3eQGLY U(B.437(3; LOGhd U(B. 75 (3;GTcGd h eNWWGJ U(B.33 (3edGMb U(B.445s
Keywords: (3GdGbJUGOs; (3GdJcGed GdEbJUGOjs; (3GdUfGYI(B- (3GdYQGbs